1996
DOI: 10.18388/abp.1996_4462
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative modification of ovalbumin.

Abstract: Stimulated neutrophils (PMNL) are a source of the active oxygen species: O2, H2O2 and HOCl/OCl- which in turn can act on proteins yielding a variety of mixed oxidation products. A system is proposed in which a model protein-ovalbumin (OVA) first undergoes chlorination by HOCl/OCl- and next is oxidised by H2O2. The modification of functional groups (-NH2, -SH, -S-S-, > C = O, Tyr and Trp) in OVA was monitored as well as their accessibility to promote aggregation. Chlorination resulted in additional inter- or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 24 publications
3
12
0
Order By: Relevance
“…HPLC analysis of chlorinated OVA which was performed prior to DTT reduction demonstrated that chlorinated OVA (2-4.5 mmol of HOCl/mg OVA) existed mainly as a monomeric protein with a molecular mass close to that of native OVA. At HOCl concentrations higher than 2.5 mmol/mg, OVA became a partially unfolded molecule [6]. Thus, our result indicates a similar chlorination of RSA as previously reported for OVA.…”
Section: Rsa Can Be Modified By Chlorinationsupporting
confidence: 90%
“…HPLC analysis of chlorinated OVA which was performed prior to DTT reduction demonstrated that chlorinated OVA (2-4.5 mmol of HOCl/mg OVA) existed mainly as a monomeric protein with a molecular mass close to that of native OVA. At HOCl concentrations higher than 2.5 mmol/mg, OVA became a partially unfolded molecule [6]. Thus, our result indicates a similar chlorination of RSA as previously reported for OVA.…”
Section: Rsa Can Be Modified By Chlorinationsupporting
confidence: 90%
“…Chlorination of CII was detected as an increase in high molecular weight bands, which are due probably to chlorination of tyrosine and lysine residues in the collagen molecule. It has been reported previously that chlorination of lysine residues in low density lipoproteins (LDL) resulted in increased aggregation of this protein [20] and has similarly increased aggregation of ovalbumin (OVA), reported as a consequence of chlorination [21]. Thus, our results indicate a similar chlorination of RCII as reported previously for LDL and OVA.…”
Section: Chlorination Of Rat Collagen IIsupporting
confidence: 89%
“…It is widely known that protein chlorination results in modification of reactive amino-acid side chains containing such functional groups as: -SH, -SS-, RSR, -NH 2 , OH (in Tyr) or indole (in Trp) (Hampton et al, 1998). Chlorination of collagen II with HOCl/OClleads to the conversion of tyrosine to dichlorotyrosine as it was observed for other proteins (Kettle, 1996;Olszowski et al, 1996). As shown in Table 1 dichlorotyrosine formation could be eas-ily traced as absorbance increase at 305-308 nm in the difference spectra of chlorinated CII.…”
Section: Resultsmentioning
confidence: 87%
“…As suggested by the HPLC, SDS/PAGE and CD data, hypochlorite chlorination was followed by CII fragmentation even at low hypochlorite concentrations (less than 1 mM). Unlike in the case of albumin (Olszowski et al, 1996) and fibronectin (Vissers & Winterbourn, 1991), for collagen this tendency seems to prevail over aggregation. The degree of CII fragmentation evaluated from CD measurements was very similar to that calculated from experiments with tritium labelled type II bovine articular collagen (Davies et al, 1993).…”
Section: Discussionmentioning
confidence: 93%